The Arabidopsis SUMO E3 Ligase AtMMS21 Dissociates the E2Fa/DPa Complex in Cell Cycle Regulation. Issue 9 (4th August 2016) - Liu, Yiyang; Lai, Jianbin; Yu, Mengyuan; Wang, Feige; Zhang, Juanjuan; Jiang, Jieming; Hu, Huan; Wu, Qian; Lu, Guohui; Xu, Panglian; Yang, Chengwei
Abstract : The Arabidopsis SUMO E3 ligase AtMMS21 dissociates the E2Fa/DPa complex by physical competition and SUMOylation in the G1/S cell cycle transition. Abstract: Development requires the proper execution and regulation of the cell cycle via precise, conserved mechanisms. Critically, the E2F/DP complex controls the expression of essential genes during cell cycle transitions. Here, we discovered the molecular function of the Arabidopsis thaliana SUMO E3 ligase METHYL METHANESULFONATE SENSITIVITY GENE21 (AtMMS21) in regulating the cell cycle via the E2Fa/DPa pathway. DPa was identified as an AtMMS21-interacting protein and AtMMS21 competes with E2Fa for interaction with DPa. Moreover, DPa is a substrate for SUMOylation mediated by AtMMS21, and this SUMOylation enhances the dissociation of the E2Fa/DPa complex. AtMMS21 also affects the subcellular localization of E2Fa/DPa. The E2Fa/DPa target genes are upregulated in the root of mms21-1 and mms21-1 mutants showed increased endoreplication. Overexpression of DPa affected the root development of mms21-1, and overexpression of AtMMS21 completely recovered the abnormal phenotypes of 35S:E2Fa-DPa plants. Our results suggest that AtMMS21 dissociates the E2Fa/DPa complex via competition and SUMOylation in the regulation of plant cell cycle.